Сверхсекретный объект: [роман] / Сергей Москвин - Москвин Сергей Львович (Спецназ ГРУ, 2004)
Экземпляры: ф11 (20180313) / Инвентарный номер: 55553 / Цена: 62.00 / Сис.шифр: Р2 / Авт.знак: М 82 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6